Predictors of Auditor Changes: The Combined Effect of Audit Characteristics and Client Governance - Cahya, Bayu Tri; Luddin, Jalal; Asyiqin, Nor'; Miranti, Liana; Hanifah, Umi (Al-Mal: Jurnal Akuntansi dan Keuangan Islam, 2024)
This study aims to analyse the effect of audit characteristics and client governance, which include audit tenure, going concern audit opinion, reputation of the Public Accounting Firm, company size, and the existence of an independent audit committee on auditor switching. This research uses a quantitative approach with an associative research type, which is sourced from the annual reports of non-financial companies listed on the Indonesian Sharia Stock Index (ISSI) and publishes its financial statements on the Indonesia Stock Exchange (IDX) for the period 2021 and 2022. The sampling technique used was purposive sampling with certain criteria, so that 46 companies were obtained as samples. The results of the analysis show that the audit tenure variable, the reputation of the Public Accounting Firm, company size, and the existence of an independent audit committee have a significant influence on auditor turnover. In contrast, going concern audit opinion does not show a significant effect on auditor turnover. The limitation of this study lies in the focus on non-financial companies listed on the ISSI, so the results may not be generalisable to other sectors. In addition, this study only considers certain variables and does not include external factors that may also affect the decision to change auditors. Future research is recommended to explore other variables that may affect auditor switching and expand the scope of research to different industry sectors to gain a more comprehensive understanding of this phenomenon.